Prognostic impact of psychoeducation program completion on inpatients with schizophrenia: a pilot cohort study - Hiroki Noguchi; Seiichiro Tarutani; Yoshiki Takei; Koichi Matsumoto; Takehiko Okamura; Hiroshi Yoneda (BMC Psychiatry)
Abstract Background Psychoeducation programs can reduce the risk of recurrence and readmission in patients with schizophrenia. However, almost all previous studies of program efficacy have included only patients completing the program, which may not be possible in all cases. The objective of this pilot cohort study was to compare the prognoses of inpatients with schizophrenia who did or did not complete a well-established institutional psychoeducation program. Methods This study is a pilot cohort study, and the participants were 32 inpatients in the psychiatric acute care ward. Among these patients, 18 completed the institutional psychoeducation program by discharge, whereas 14 missed one or more sessions for various reasons. The primary outcome was the duration of outpatient treatment (DOT) during the 5-year follow-up period, and the secondary outcomes were comparisons of the risk of all-cause discontinuation for outpatient treatment and correlations between the program participation rates and DOT. Results DOT was significantly longer in the program completion group than in the noncompletion group (918.2 (174.3) days vs. 225.5 (35.7) days, p = 0.001), and multivariate Cox proportional hazards regression analysis revealed that program noncompliance was associated with a 4.450-fold (p = 0.002) greater risk of discontinuation of outpatient treatment according to multivariate analysis. A significant weak correlation was found for DOT and rates of sessions admitted to the programme (Pearson's r = 0.384, p = 0.030). Conclusions Completion of a psychoeducation program could enhanced the success of outpatient treatment. As psychoeducation and related factors may have a positive effect of the prognosis after discharge, inpatient psychoeducation programs should be flexible enough to provide opportunities for completion.